Developing Youth Competencies through Waqf Mechanisms:A Comprehensive Literature Review for Enhancing the Islamic Economy - Wali Saputra (Indo Publishing, 2025)
This investigation seeks to systematically analyze the function and potential of waqf mechanisms in the development of youth competencies to fortify the Islamic economy. Employing the Systematic Literature Review (SLR) methodology, the research scrutinized 32 scholarly articles published from 2013 to 2024, sourced from prominent databases including Scopus, ScienceDirect, and Google Scholar. The findings indicate that waqf plays a pivotal role in financing skills training initiatives, fostering youth entrepreneurship, and enhancing access to vocational education through both traditional and digital means. Concepts such as waqf-based incubators, digital waqf, and waqf crowdfunding emerge as pertinent innovations to tackle the challenges faced by Muslim youth in a competitive global economic landscape. Nonetheless, several challenges were also recognized, including inadequate waqf literacy among youth, constraints posed by existing regulations, and a lack of synergy between waqf institutions and educational or training entities. The study advocates for the establishment of affirmative regulatory frameworks, the enhancement of institutional capacity within waqf entities, and the implementation of inclusive waqf literacy campaigns as strategies to cultivate a sustainable and equitable Islamic economic ecosystem. This research contributes significantly to the corpus of Islamic economic literature and paves the way for empirically-driven advanced inquiries.